Delayed diagnosis of disseminated tuberculosis in pregnancy: a case report - Vinod, Sushmita; Vadivelu, Gangadharan; Mani, Anbumaran Parivakkam (International Journal of Advances in Medicine, 2022)
Miliary tuberculosis (TB) is a lethal form of TB, if left untreated. Miliary TB accounts for <2% of all cases of TB in immunocompetent individuals. Intracranial tuberculoma is a rare manifestation of Mycobacterium tuberculosis (MTB), seen in only 1% of TB patients. It can occur as single or multiple lesions, most commonly located in the frontal and parietal lobes. Clinical features mimic that of any space-occupying lesion in the brain. In pregnant women, diagnosis of TB may be delayed by the non-specific nature of early symptoms and because they are often attributed to pregnancy.Here we report one such case where the diagnosis of TB was delayed due to the non-specific nature of her symptoms in ante-natal period.